Barriers and Opportunities for Promoting Health Professions Careers among Latinxs in the Midwest. Issue 2 (15th March 2023) - Johansson, Patrik; Tutsch, Sonja; King, Keyonna; De Alba, Armando; Lyden, Elizabeth; Leon, Melissa; Schober, Dan
ABSTRACT: Latinx populations experience health disparities and are underrepresented among health professionals. One strategy to address these health disparities includes increasing the proportion of Latinx health professionals. The purpose of this study was to examine barriers and facilitators for Latinxs in pursuing health professions careers in a Midwestern state experiencing dramatic increases in Latinx populations, especially in rural areas. We conducted focus groups with Latinx high school, undergraduate, and graduate health professions students in rural and urban settings to examine barriers and opportunities for promoting health professions careers. Although many of our results confirm findings from other studies, novel future directions for this work should include comprehensive interventions that span the health professions education pipeline, including interventions that engage Latinx parents. A need also exists for increased representation of Latinx science teachers, counselors, staff, faculty, and particularly senior administrators in academic settings, from high school to graduate health professions schools to serve as role models, mentors, and advocates for Latinx health professions students. Educational programming of this magnitude requires institutional commitment to diversity, driven by leadership, with an explicit commitment to workforce and student diversity.